Analysis of Factors Influencing Library Financing Serbajadi 1st State Senior High School - Suwandi, Suwandi; Siahan, Amirrudin; Akhir, Muhammad; Nasution, Asrul; Salam Nasution, Abdul (Green Publisher Indonesia, 2022)
This study aims to find out how the library facilities and infrastructure at SMA 1 Negeri Serbajadi are, then to find out how the interest in visiting students is and to find out whether or not there is an influence between library facilities and infrastructure on students' interest in visiting SMA 1 Negeri Serbajadi. This research is a quantitative research. A sample of 249 students using the Simple Random Sampling technique. Data collection techniques using questionnaires and documentation. Data processing techniques using descriptive analysis techniques and inferential analysis. The results showed that there was no influence between the intensity of student arrivals and library costs which showed a negative correlation of -0.363. There was a simultaneous effect between the availability of library books on library costs for class XI students at the SMA N 1 Serbajadi Library by 32%. So that the increase in the availability of library books will affect the increase in library support costs for class XI students in the library of SMA N 1 Serbajadi. There is an effect of library facilities on library costs for class XI students in the library of SMA N 1 Serbajadi with a partial contribution value of 48.2%. So the better the library facilities, the higher the student library costs. There is an effect of library management on library costs for class XI students in the SMA N 1 Serbajadi library with a partial contribution value of 2.5%. So the more library services increase, the student library costs also increase. There is an effect of library services on library costs for class XI students in the SMA N 1 Serbajadi library with a partial contribution value of 5.83%. So the more library services increase, the student library costs also increase.